Desempenho mastigatório e sua associação com a condição dentária e o uso de prótese dentária em idosos institucionalizados - Daniella Agresta Lovato da Silva (2024)
This study evaluated the associations between the masticatory performance of institutionalized elderly individuals with oral health conditions and the use of dental prostheses. For this purpose, a cross-sectional study was conducted with a sample of 193 elderly individuals living in philanthropic Long-Term Care Institutions in the city of Belo Horizonte, Minas Gerais. Oral health conditions were assessed through clinical examinations, including the presence of caries, edentulism, use of dental prostheses, and functional dentition. The masticatory performance of the elderly was measured using the two-color mixing ability method of chewing gum. The elderly were asked to chew the gum for 20 chewing cycles, after which the chewed gum was pressed and scanned. The image of the chewed gum was analyzed by the software ViewGum©. The data were initially evaluated by describing the absolute values (n) and percentages (%) of all variables, considering the correction for design effect, using the software STATA® 14.0. Subsequently, bivariate analysis was performed for all independent variables, and variables with a p-value less than 0.20 were considered in the multilevel analysis, with the Odds ratio and confidence interval (95% CI) also estimated.The results showed that half of the elderly have a deficiency in mastication (49.2%), the majority are edentulous (69.4%), lack functional dentition (94.8%), do not have dental caries (81.85%), and half do not use dental prostheses (52.8%). Among the elderly who use prostheses, most use only a total prosthesis in one of the arches (30.05%). Regarding masticatory performance, only 9.33% of the elderly exhibit excellent masticatory performance. The best masticatory performance is related to the presence of teeth, functional dentition, and the use of dental prostheses in both arches or a combination of fixed and removable prostheses (PF and PPR). The multilevel analysis identified a significant difference only in age (p<0.003), edentulism (p<0.0001), and the use of dental prostheses in both dental arches (p<0.0001). Therefore, this study shows that older elderly individuals have worse masticatory performance, and the presence of teeth and the use of dental prostheses in both arches are important for satisfactory masticatory performance.